Pengaruh Jumlah Pembiayaan, Pendapatan Nasabah, dan Jangka Waktu Pengembalian terhadap Kelancaran Pembiayaan Nasabah BPRS Carana Kiat Andalas Bukittinggi - Adif, Riandy Mardhika; Annuara, Muhammad; Irsadunas (SAFE-Network, 2022)
This study aims to determine the effect of the amount of financing, customer income and the period of return on customer financing at BPRS Carana Kiat Andalas Bukittinggi. This study used a quantitative method with a questionnaire research instrument with a logistic regression analysis tool from SPSS 22. The sampling method used purposive sampling with the slovin technique, with a total population of 743 financing customers at BPRS Carana Kiat Andalas Bukittinggi and a sample of 80 financing customers at BPRS Carana Tips Andalas Bukittinggi. The results of this study indicate that the amount of financing has a negative influence on the smooth return of financing. Customer income has a positive influence on the smooth return of financing. Meanwhile, the payback period does not affect the smooth return of financing at BPRS Carana Kiat Andalasa Bukittinggi. And simultaneously the variable amount of financing, customer income, and payback period affect the smooth return of financing at BPRS Carana Kiat Andalas Bukittinggi.